Hubungan Antara Pengetahuan, Dukungan Keluarga Dan Sarana Terhadap Keaktifan Lanjut Usia Mengikuti KegiatanPosyandu Lansia Bagas Waras Di Desa Pabelan - , Hetik, H.M Abi Muhlisin, SKM., M. Kep (2017)
Posyandu is a forum for communication, technology transfer, and health services by people and for people who have a strategic value for the development of human resources, especially the elderly. IHC Elderly Bagas Sane is one posyandu located in Dukuh Village Pabelan Subdistrict Tegal Mulyo Kartasura where the number of elderly in the activeness of Posyandu activities is relatively low. Based on preliminary observations of research, several factors are assumed to be related to the activity of the elderly in participating in Posyandu elderly Posyandu program Bagas Sane is knowledge of the elderly, family support and completeness of facilities and infrastructure posyandu. This study aims to determine the relationship between knowledge about the benefits of integrated health, family support facilities, with liveliness elderly in participating in Posyandu activities Bagas Sane elderly Dukuh Village Tegalmulyo Pabelan District of Kartasura. This research is quantitative research with correlative descriptive method with cross sectional approach. The study population is elderly Posyandu Bagas Sane Pabelan Kartasura, while the study sample was 54 people who obtained using simple random sampling method. Collecting data using questionnaires, while data analysis using Spearman rank test. Conclusion of the study is the knowledge of the elderly about the benefits of Posyandu elderly is largely lacking (43%), family support for the activity of the elderly in participating in Posyandu elderly mostly moderate (41%), means available to the facility Posyandu elderly is largely lacking (41% ), active elderly in participating in posyandu activities are mostly inactive (52%), and there is a relationship of knowledge elderly, family support and infrastructure to the liveliness of the elderly following the posyandu elderly posyandu in Bagas Sane Pabelan Kartasura. Keywords: elderly liveliness, knowledge, family support, infrastructure,Posyandu,